Factors influencing faculty job satisfaction: a quantitative study of private medical colleges in Karachi - Asad Ali Khan; Shamsul Arfin Qasmi; Muhammad Abid; Khushk, Imdad Ali (Journal of the Pakistan Medical Association, 2024)
Objective: To identify key factors influencing academic job satisfaction among faculty members of private medical colleges in an urban setting. Method: The cross-sectional, quantitative study was conducted from October to November 2021 at the Department of Community Health Sciences, Fazaia Ruth Pfau Medical College, Karachi, and comprised faculty members associated with 13 private medical colleges in Karachi. Data was collected using a 32-item questionnaire that was scored on a 5-point Likert scale. Key predictors of job satisfaction were identified and evaluated. Data was analysed using SPSS version 23. Results: Of the 200 subjects surveyed, 106(52.7%) were males. The overall mean age was 29.4±5.2 years. There were 145(72.5%) respondents who were married, 106(53%) had employed spouses, 102(551%) were either professors or associate professors, and 93(46.5%) had professional experience of 1-5 years. Three principal factors were identified; career growth opportunities, working conditions and compensatory packages (p<0.001). The lowest mean satisfaction score was observed for compensatory packages (1.74±0.84), followed by working conditions (2.28±1.41) and career growth (2.38±1.39). Conclusion: Improving compensatory packages, working conditions and career growth opportunities were found to be crucial for enhancing job satisfaction among faculty members in Karachi-based private medical colleges. Key Words: Job satisfaction, Faculty, Private medical colleges, Karachi, Factor analysis.